Association between visceral adiposity index and sleep disorders among the U.S. adults: a cross-sectional study - Liu, Chunhua; Qiu, Linan; Wang, Tingting; Ye, Zegen; Wu, Simin; Li, Di; Lin, Huajian; Jin, Yue (Frontiers in Neurology, 2025)
BackgroundThe visceral adiposity index (VAI) reliably measures body fat distribution and related dysfunctions. However, its association with sleep disorders among US adults remains unclear.MethodsThis study analyzed cross-sectional data from the 2005 to 2018 National Health and Nutrition Examination Survey (NHANES) for adults aged 18 and older. We used multivariable logistic regression to evaluate the association between VAI and sleep disorders and applied restricted cubic splines to assess potential non-linear relationships. Additionally, subgroup analyses by gender, age, and race were conducted to explore the VAI-sleep disorder association across different populations.ResultsThis study included 14,021 adults aged 18 +. In Model 1, adjusted for gender and age, each unit increase in VAI was associated with a 5% higher risk of sleep disorders (OR = 1.05; 95% CI = 1.02–1.07). In Model 2, which adjusted for all potential confounders, each unit increase in VAI was linked to a 3% higher risk (OR = 1.03; 95% CI = 1.00–1.05). When treating VAI as a categorical variable, those in the highest quartile (Q4) had a 21% higher risk of sleep disorders compared to those in the lowest quartile (Q1) (OR = 1.21; 95% CI 1.03–1.41). Restricted cubic spline analysis revealed a positive linear relationship between VAI and sleep disorder prevalence. Subgroup analysis found stronger associations in males and non-Hispanic white individuals.ConclusionWhile causality cannot be confirmed, this cross-sectional study shows a significant positive linear association between higher VAI and the risk of sleep disorders among U.S. adults.